2016
DOI: 10.1189/jlb.5ru0816-341r
|View full text |Cite
|
Sign up to set email alerts
|

A protective role of IL-37 in cancer: a new hope for cancer patients

Abstract: IL-37 is a cytokine belonging to the IL-1 family. Although discovered in silico in 2000, significant advances in the understanding of its biology were made only in recent years. It is a member of the family with potent anti-inflammatory and immunosuppressive properties. It is produced as a precursor without a classic signal peptide. The precursor is cleaved into mature form in the cytoplasm by caspase-1. A small fraction of the cleaved IL-37 binds SMAD-3, translocates to the nucleus, and suppresses transcripti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
41
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(48 citation statements)
references
References 87 publications
0
41
0
1
Order By: Relevance
“…IL‐37 has shown anti‐inflammatory and immune suppression effects. IL‐37 contributes to the immunosuppressive property of human regulatory T cells, and its antitumor activity was identified by the recruitment of more natural killer cells in hepatocellular carcinoma 11, 13. In addition, we found that low IL‐37 expression and dMMR status are associated with high CD66b + TAN levels in CRC.…”
Section: Discussionmentioning
confidence: 64%
See 1 more Smart Citation
“…IL‐37 has shown anti‐inflammatory and immune suppression effects. IL‐37 contributes to the immunosuppressive property of human regulatory T cells, and its antitumor activity was identified by the recruitment of more natural killer cells in hepatocellular carcinoma 11, 13. In addition, we found that low IL‐37 expression and dMMR status are associated with high CD66b + TAN levels in CRC.…”
Section: Discussionmentioning
confidence: 64%
“…Nevertheless, entirely distinct with most IL‐1 family members, that are characterized with proinflammatory functions, IL‐37 has emerged as an important inhibitor of the innate immune response. With the accumulated evidence, IL‐37 has been recognized as a typical anti‐inflammatory cytokine related to autoimmune diseases, endotoxemia, inflammatory liver injury, obesity, and cancer 8, 9, 10, 11, 12. Gao et al9 found that the intratumoral injection of IL‐37 inhibited tumor growth and the antitumor activity of IL‐37 was abrogated in mice models.…”
Section: Introductionmentioning
confidence: 99%
“…It has been well established that inflammation is closely related to carcinogenesis . As an anti‐inflammatory cytokine, many studies have suggested the antitumor role of IL‐37 in various tumor types, which have been reviewed previously . Here, we will describe the most recent progress for the role of IL‐37 in fibrosarcoma, breast cancer, lung cancer, ovarian cancer, renal cell carcinoma (RCC), oral squamous cell carcinoma (OSCC), cervical cancer, colon cancer, multiple myeloma (MM), prostate cancer, and HCC.…”
Section: Il‐37 In Tumormentioning
confidence: 96%
“…Conversely, anti‐inflammatory IL‐37 might suppress tumorigenesis by inhibiting protumorigenic inflammation. Indeed, the protective role of IL‐37 in cancer has been reported when IL‐37 was transfected into cancer cells, or when recombinant IL‐37 was administered in animal models of cancers (summarized in review papers by Ding et al and Abulkhir et al). However, only limited studies have used cancer patient samples to investigate IL‐37 .…”
Section: Introductionmentioning
confidence: 99%